Anomaly of spontaneous transition to instability of liquid–vapour front in a porous medium. (May 2015) - Khan, Zafar Hayat; Pritchard, David
Abstract: In this article, we have investigated the instability of the liquid–vapour front in a geothermal system with isothermal boundaries. A two–dimensional linear stability analysis of the isothermal basic state shows that the Rayleigh–Taylor mechanism is the dominant contributor to instability. A conditional expression for the critical modified Rayleigh number for different heat transport processes has been found. It has been shown that the spontaneous transition to instability is an artefact of neglecting thermal advection and the imposition of the phase change front to be equidistant from the liquid and vapour boundaries.